2013
DOI: 10.3168/jds.2012-5877
|View full text |Cite
|
Sign up to set email alerts
|

Preference and drinking behavior of lactating dairy cows offered water with different concentrations, valences, and sources of iron

Abstract: Drinking water can contain high concentrations of Fe, mainly of the ferrous (Fe(2+)) valence. The current recommended upper tolerable concentration of Fe in drinking water for cattle (0.3mg/L) comes from guidelines for human palatability, but cattle may be able to tolerate higher concentrations. Our objective was to determine the effects of varying concentrations of ferrous (Fe(2+)) or ferric (Fe(3+)) iron and Fe salt source on lactating dairy cows' preferences for and drinking behavior of water offered as cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…Lowered milk and fat production in dairy cattle dosed orally with 30 to 60 g of Fe/d in the form of ferric hydroxide (Coup and Campbell, 1964) was reported. Genther and Beede (2013) reported lowered water intake by lactating cows with 8 mg of Fe/L drinking water. Water Fe of the same magnitude as in the current study might reduce water intake due to palatability, potentially affecting production.…”
Section: Milk Production and Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lowered milk and fat production in dairy cattle dosed orally with 30 to 60 g of Fe/d in the form of ferric hydroxide (Coup and Campbell, 1964) was reported. Genther and Beede (2013) reported lowered water intake by lactating cows with 8 mg of Fe/L drinking water. Water Fe of the same magnitude as in the current study might reduce water intake due to palatability, potentially affecting production.…”
Section: Milk Production and Compositionmentioning
confidence: 99%
“…Excess iron available in the intestinal tract can interfere with absorption of other minerals and may cause oxidative stress, bacterial infection, diarrhea, and reduced weight gain (Coup and Campbell, 1964;Standish et al, 1971;Bullen et al, 1978;McGuire et al, 1985;Hansen et al, 2010). Genther and Beede (2013) reported lower water intake in lactating cows abomasally infused with ferrous lactate equivalent to 8 mg of Fe/L of drinking water. Iron is the third most frequent and important anti-quality consideration for dairy cattle and Fe toxicity is sometimes exacerbated in transition cows and fresh cows (Beede, 2005).…”
Section: Introductionmentioning
confidence: 97%
“…No significant difference (P > 0.05) was noted in milk yield when cattle were infused with iron treatments (Feng et al, 2013). It is known that the amount of iron in water can affect the palatability of the water (National Primary Drinking Water Regulations, 2011) and cows that are on restricted water intake, whether from lack of availability (drought) or lack of willingness to consume (metallic flavor) may produce less milk (Genther and Beede, 2013).…”
Section: Experiments 4 (Case Study): Effect Of Low and High Iron Sourcmentioning
confidence: 99%
“…Due to high levels of water needed per cow, it is likely that high (above EPA secondary standards) iron content in water (>0.3 mg/kg) could influence milk composition and oxidative stability (National Primary Drinking Water Regulations, 2011). Genther and Beede demonstrated that metallic flavors in milk, as occurs at the EPA SMCL, may cause cattle to consume less water and produce less milk (Gary et al, 2007;Genther and Beede, 2013).…”
Section: Implication Of Iron In Bovine Nutritionmentioning
confidence: 99%
“…Die empfohlene Fe-Konzentration für Tränkewasser liegt unter 3 mg/l. Ab einer Fe-Konzentration von > 10 mg/l wird die Schmackhaftigkeit und damit die Aufnahme durch Tiere maßgeblich beeinträchtigt (Übersichten bei [15] [16]).…”
Section: Tränkewasserunclassified